Keragaman Pangan dan Tingkat Kecukupan Energi serta Protein Pada Balita - Dwi Putri Pangesti Suryo Andadari; Trias Mahmudiono (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2017)
Background: Childrens needs adequacy nutrients to support the growth process. Nutritional needs in children period can be fullfiled by consuming a variety of foods. Agricultural and pond dominated area can to provide adequate food availability. Objectives: The purpose of this study is to analyze the differences of dietary diversity and the level of energy and protein adequacy in children in agricultural and pond dominated areas. Method: This cross sectional study design and samples are 55 children under five years with the mothers/babysitters as respondents. Samples are taken using proportional random sampling. Dietary diversity are assessed using Individual Dietary Diversity Score (IDDS) with the criteria considered to consume if the amount minimum 10 grams. Adequacy energy and protein is assessed using food recall 2×24 hours and continued by compared with AKG. The differences of dietary diversity, energy ad protein adequacy rates are analyzed using Mann Whitney Test. Results: The results shows that children in agricultural area classified low dietary diversity and middle dietary diversity in children pond dominated area (p=0.024). Children in agricultural and pond dominated areo classified less energy adequate (0.588) and more protein adequacy (0.459). Conclusion: There is difference of dietary diversity at children in agricultural and pond dominated area and ther is no difference of energy and protein adequacy in children in agricultural and pond dominated area.ABSTRAK Latar Belakang: Pada masa balita membutuhkan asupan gizi yang mencukupi untuk menunjang proses tumbuh kembang tersebut. Kebutuhan gizi pada balita dapat dipenuhi dengan mengonsumsi makanan yang beragam. Pemenuhan pangan yang cukup tercermin dari ketersediaan pangan yang cukup. Sumber daya pertanian dan perikanan seperti tambak memiliki potensi untuk menyediakan sumber pangan.Tujuan: Tujuan penelitian ini untuk menganalisis perbedaan keragaman pangan dan tingkat kecukupan energi dan protein pada balita di wilayah pertanian dan tambak.Metode: Penelitian cross sectional ini menggunakan sampel sebanyak 55 balita dengan ibu/pengasuh sebagai responden. Sampel diambil menggunakan proportional random sampling. Keragaman pangan dinilai menggunakan Individual Dietary Diversity Score (IDDS) dan dinilai dengan kriteria minimum konsumsi 10 gram. Data konsumsi pangan dikumpulkan menggunakan food recall 2×24 jam kemudian dikonversi dibandingan dengan Angka Kecukupan Gizi (AKG) untuk mendapatkan Tingkat Kecukupan Energi dan Tingkat Kecukupan Protein. Data dianalisis menggunakan Mann Whitney Test.Hasil: Hasil penelitian menunjukkan bahwa balita di wilayah pertanian tergolong keragaman pangan rendah dan balita di wilayah tambak tergolong keragaman pangan sedang (p=0,024). Balita di wilayah pertanian maupun tambak tergolong tingkat kecukupan energi kurang (p=0,588) dan tingkat kecukupan protein (p=0,459).Kesimpulan: Terdapat perbedaan keragaman pangan minimum konsumsi 10 gram diterapkan pada balita di wilayah pertanian dan tambak dan tidak terdapat perbedaan kecukupan energi serta protein pada balita di wilayah pertanian dan tambak.